2021
DOI: 10.1038/s41598-021-00026-x
|View full text |Cite
|
Sign up to set email alerts
|

MinION sequencing from sea ice cryoconites leads to de novo genome reconstruction from metagenomes

Abstract: Genome reconstruction from metagenomes enables detailed study of individual community members, their metabolisms, and their survival strategies. Obtaining high quality metagenome-assembled genomes (MAGs) is particularly valuable in extreme environments like sea ice cryoconites, where the native consortia are recalcitrant to culture and strong astrobiology analogues. We evaluated three separate approaches for MAG generation from Allen Bay, Nunavut sea ice cryoconites—HiSeq-only, MinION-only, and hybrid (HiSeq +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 116 publications
(188 reference statements)
0
5
0
Order By: Relevance
“…Though several studies reported diversity and succession of microbial communities across the different GF ecosystems (Kim et al 2017 ; Schuette et al 2010 ; Schütte et al 2009 ; Venkatachalam et al 2021 ), only a few studies investigated functions and processes associated with microbial communities (Nash et al 2018 ; Varliero et al 2021 ). In particular, reconstructing MAGs directly from soil samples provides unique opportunities to study individual community members, their metabolisms, and their survival strategies (Maggiori et al 2021 ). In particular, the samples collected from the extreme environmental region are often much more difficult to cultivate in the laboratory in comparison to other tropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Though several studies reported diversity and succession of microbial communities across the different GF ecosystems (Kim et al 2017 ; Schuette et al 2010 ; Schütte et al 2009 ; Venkatachalam et al 2021 ), only a few studies investigated functions and processes associated with microbial communities (Nash et al 2018 ; Varliero et al 2021 ). In particular, reconstructing MAGs directly from soil samples provides unique opportunities to study individual community members, their metabolisms, and their survival strategies (Maggiori et al 2021 ). In particular, the samples collected from the extreme environmental region are often much more difficult to cultivate in the laboratory in comparison to other tropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…The sediment and meltwater above remain in approximate equilibrium of the glacier surface, usually tens of centimeters below the surface [162,145]. Despite their small size and dynamic conditions, cryoconite holes host actively growing microbial communities [163], and the viruses that parasitize them [148,164]. Although viral production rates in Arctic cryoconite holes have been measured as similar to other sediments around the globe, microscopy-suggested burst sizes were substantially lower (only 2-4 viruses cell -1 ).…”
Section: Viruses In Cryoconite Holesmentioning
confidence: 99%
“…Furthermore, based on the BUSCO analysis (Figure 1c), the newly assembled genome has better completeness indices and fewer duplicated, fragmented, and missing genes. Similarly, Maggiori et al (2021) demonstrated that by using a hybrid assembly approach (HiSeq + MinION), it was possible to obtain a greater number of genomes from metagenomic samples, with longer contigs, more coding sequences, higher completeness, less contamination, and higher N50 [66].…”
Section: Genome Assembly and Assessmentmentioning
confidence: 99%